Pemenuhan Hak Restitusi Terhadap Anak Korban Tindak Pidana Kejahatan Seksual (Studi Penelitian Pengadilan Negeri Medan Kelas I-A Khusus) - Muhammad Mitra Lubis (Jurnal Hukum dan Kemasyarakatan Al-Hikmah, 2020)
AbstractRestitution is the payment of compensation which is charged to the offender based on a court decision that has permanent legal force for material and / or material losses suffered by the victim or his heir. In the PP it is stated that every child who is a victim of a criminal offense is entitled to get restitution.The problems here are: rules of restitution rights in the Indonesian legal system, judicial legal considerations in fulfilling the right of resitution to children victims of sexual crimes in the jurisdiction of the Medan Class IA Special District, application of restitution rights as well as obstacles and efforts to fulfill restitution rights against children victims of sexual crimes in Medan, especially in the jurisdiction of Medan Special Class IA PN.This research is descriptive with a normative juridical approach. "The normative juridical approach is to emphasize the science of law with a focus on secondary data, in the form of primary, secondary and tertiary legal materials", and to complete the data carried out by collecting relevant materials and conducting a literature study in which the data will then be analyzed in a manner juridical.It was concluded that the rules of restitution rights in the legislation contained in the Criminal Procedure Code, Criminal Code, Law on Consumer Protection, Human Rights Court, Eradication of Corruption, Eradication of Terrorism, Eradication of Trafficking in Persons, Protection of Witnesses and Victims, Environmental Protection and Management Living Government Regulations Provision of Compensation, Restitution and Assistance to Witnesses and Victims, Compensation and Rehabilitation of Victims of Gross Human Rights Violations. Judges' legal considerations in fulfilling the right of re-constitution of child victims of sexual crimes in the jurisdiction of the Medan Class I-A Special District Court, especially in the form of compensation, whether through compensation and / or restitution should receive the attention of policy makers. Actually criminal fines need not be included in the Child Protection Act. What should be included is something that can accommodate the interests of children as victims of sexual crimes, namely restitution. Then an idea arises that the community is given an opportunity. The application of restitution rights, obstacles and efforts to fulfill rights by investigators and the Public Prosecutor play a very important role in the submission of evidence to support victims' rights to get restitution. Recalling the Judge who would later consider the amount of restitution obtained by the victim as outlined in the decision.Keywords: Restitution Rights, Victims, Criminal Acts, Sexual Crimes.   AbstrakRestitusi merupakan pembayaran ganti kerugian yang dibebankan kepada pelaku berdasarkan putusan pengadilan yang berkekuatan hukum tetap atas kerugian materiil dan atau immateriil yang diderita korban atau ahli warisnya. Dalam PP disebutkan bahwa setiap anak yang menjadi korban tindak pidana berhak memperoleh restitusi.Permasalahan disini adalah: aturan hak restitusi dalam sistem perundang-undangan di Indonesia, pertimbangan hukum hakim dalam pemenuhan hak resititusi terhadap anak korban tindak pidana kejahatan seksual di wilayah hukum PN Medan Kelas I-A Khusus, penerapan hak restitusi serta hambatan dan upaya pemenuhan hak restitusi terhadap anak korban tindak pidana kejahatan seksual di kota medan terutama di wilayah hukum PN Medan Kelas I-A Khusus.Penelitian ini bersifat deskriptif dengan pendekatan yuridis normatif. “Pendekatan yuridis normatif yaitu menekankan pada ilmu hukum dengan menitik beratkan pada data sekunder, yang berupa bahan hukum primer, sekunder, dan tertier”, dan untuk melengkapi data dilakukan dengan mengumpulkan bahan-bahan yang relevan dan melakukan studi pustaka yang selanjutnya data akan dianalisis secara yuridis.Disimpulkan bahwa aturan hak restitusi dalam perundang-undangan tertuang dalam KUHAP, KUHP, Undang-Undang tentang Perlindungan Konsumen, Pengadilan HAM, Pemberantasan TPK, Pemberantasan Tindak Pidana Terorisme, Pemberantasan TPPO, Perlindungan Saksi dan Korban, Perlindungan dan Pengelolaan Lingkungan Hidup Peraturan Pemerintah Pemberian Kompensasi, Restitusi dan Bantuan kepada Saksi dan Korban, Kompensasi dan Rehabilitasi terhadap Korban Pelanggaran HAM Berat. Pertimbangan hukum hakim dalam pemenuhan hak resititusi terhadap anak korban tindak pidana kejahatan seksual di wilayah hukum Pengadilan Negeri Medan Kelas I-A Khusus, khususnya yang berupa ganti kerugian, baik melalui pemberian kompensasi dan/atau restitusi seharusnya memperoleh perhatian dari pembuat kebijakan. Sebenarnya pidana denda tidak perlu dimasukkan dalam UU Perlindungan Anak. Adapun yang seharusnya dimasukkan adalah sesuatu hal yang dapat mengakomodir kepentingan anak selaku korban kejahatan seksual, yaitu restitusi. Kemdian muncul ide masyarakat diberi kesempatan. Penerapan hak restitusi, hambatan dan upaya pemenuhan hak oleh penyidik maupun Penuntut Umum memegang peranan yang sangat penting dalam pengajuan bukti untuk menunjang hak korban mendapatkan restitusi. Mengingat Hakim yang nantinya akan mempertimbangkan jumlah restitusi yang didapatkan oleh korban yang dituangkan dalam amar putusan.Kata Kunci  : Hak Restitusi, Korban, Tindak Pidana, Kejahatan Seksual.